PROFIL TNF-Î± SESUDAH SENAM LANSIA PADA LANSIA DI PANTI WREDHA BETHANIA LEMBEAN KOTA MANADO - Tulong, Michael; Supit, Siantan; Engka, Joice N. A. (eBiomedik, 2015)
Abstract: Tumor Necrosis Factor- ? (TNF-?) is a systemic pro-inflammatory cytokine which is responsible to a trauma, injury, or inflammation in human body. Physical activity can physiologically affect the human body, inter alia the immune system. This was an experimental study with a post test design. This study aimed to determine the profile of TNF-? after doing gymnastics among the elderly at nursing home Bethania Lembean. Samples included 30 peoples who met the inclusion criteria, i.e. over 64 years old, followed the gymnastics for 5 weeks regularly, approbated as respondents, healthy, and signed the informed consent. The TNF-? concentration measurements were done by using enzyme-linked immunosorbent assay (ELISA) Quantikine ®Human TNF-?. The results showed that the average conventration of TNF-? after elderly gymnastics was 70.54 pg/ml, with the highest value of 88.90 pg/mL and the lowest value of 12.54 pg/mL. For all respondents, TNF-? was within normal limit and ranged between 10-100 pg / mL. Conclusion: In this study, TNF-? concentrations after elderly gymnastics for 5 weeks were within normal limitsKeywords: TNF-?, elderly gymnasticsAbstrak: Tumor Necrosis Factor-? (TNF-?) merupakan suatu sitokin sistemik pro-inflamasi, yang berespons terhadap suatu cedera trauma atau peradangan yang terjadi dalam tubuh manusia. Kegiatan fisik dapat berdampak cukup besar pada tubuh manusia, dimana dapat merubah sistem imun tubuh secara fisiologis. Penelitian ini bersifat eksperimental dengan rancangan post test design dan bertujuan untuk mengetahui profil TNF-? sesudah senam lansia di Panti Wredha Bethania Lembean. Sampel penelitian berjumlah 30 orang yang memenuhi kriteria inklusi yaitu berumur di atas 64 tahun, teratur mengikuti senam lansia selama 5 minggu, bersedia menjadi responden, sehat saat di periksa, dan menandatangani informed consent. Pengukuran konsentrasi TNF-? di lakukan dengan menggunakan enzyme-linked immunosorbent assay (ELISA) Quantikine ®Human TNF-?. Hasil penelitian memperlihatkan bahwa rerata kadar TNF-? sesudah senam lansia 70,54 pg/ml, dengan nilai tertinggi 88,90 pg/mL dan nilai terendah 12,54 pg/mL. Berdasarkan hasil yang di dapat, semua kadar TNF-? masih dalam batas normal dengan nilai 10-100 pg/mL. Simpulan: TNF-? sesudah senam lansia selama 5 minggu masih dalam batas normal.Kata kunci:TNF-?, senam lansia